Beberapa Faktor yang Terjadi pada Gangguan Gizi pada Anak di Puskesmas Maubesi, Nusa Tenggara Timur: Studi Kohort Retrospektif: Hasil Penelitian - Saudale, Yunri Steviani (Cermin Dunia Kedokteran, 2025)
Introduction: In Indonesia, the incidence of nutritional disorders (malnutrition) in children aged 0–59 months in 2023 reached 8.5%. Methods: A retrospective cohort study was conducted on 48 children in the Maubesi Health Center working area, East Nusa Tenggara, in January–June 2024 to assess the relationship between gender, birth weight and length, number of siblings, place of birth, exclusive breastfeeding, immunization status, medical history, food variation, mother’s age and education, mother’soccupation, mother’s weight before pregnancy, mother’s Hb levels during pregnancy, mother’s history of hypertension and diabetes, and antenatal care (ANC) visits with the incidence of malnutrition and severe malnutrition. Data were obtained from the Integrated SIGIZI application, and children’s nutritional status was measured using the WHO (2006) weight-for-height chart. Results: Theanalysis used Fisher’s exact test and Spearman’s rank correlation test. A significant relationship was found between the number of ANC visits and the incidence of both malnutrition and severe malnutrition (p = 0.001), which showed a weak negative correlation: r(44) = -0.139, p = 0.357. Conclusion: In this study, a negative correlation was obtained between the number of ANC visits andthe incidence of undernutrition and severe malnutrition.